The Effect of Single and Combination Sterilization on In Vitro Culture of Kepel (Stelechocarpus burahol Hook F. & Thomson) Nodes - Hutabarat, Cindy Talenta; Restiani, Ratih; Prasetyaningsih, Aniek (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022)DO - 10.24843/metamorfosa.2022.v09.i02.p02, 2022)
Kepel is identity of Yogyakarta's flora with potential in the health sector and the field of building material construction. Kepel is reported to be in the Conservation dependent category, which means it is difficult to find (rare). In vitro culture is a plant propagation technique using parts of the plant aseptically. In vitro culture can produce a large number of plants in a short time. This is very much needed in efforts to conserve kepel plants. The main thing that determines the success of the in vitro culture process is sterilization. This study aims to determine the effect of single and combined sterilants with various treatments for soaking time. The explants used in this study were young Kepel plant nodes ex-vitro in the age range of 1-2 years. In this study, 3 groups were consisting of control, 10% chlorox single sterilant with an immersion time of 10, 15, and 20 minutes, 70% ethanol with an immersion time of 1, 3, and 5 minutes, carbendazim 5% with an immersion time of 10, 15, and 20 minutes and a combination sterilant (10% chlorox + 70% ethanol + 5% carbendazim) with immersion time of 1 minute 30 seconds, 3 minutes 30 seconds and 5 minutes 30 seconds. Parameters observed during the time of contamination, percentage of contamination, type of contamination, and successful explants were observed for 21 days. The results showed that a combination sterilant of 5 minutes 30 seconds was more optimal than a single sterilant in suppressing contamination of the nodal explants of the Kepel plant, with contaminants appearing time of 8-29 (HST), the percentage of contamination 66%, the type of fungal contamination 66.66% and explants growing (callus) 100%.